Hello!
The answer is:
The correct option is D.
![\sqrt{3^(15) }=3^(7)* √(3)](https://img.qammunity.org/2020/formulas/mathematics/college/ul2vvbmos2dqbhued956ia6uzjvc8q5ne4.png)
Why?
To solve this problem, we must remember the following properties:
Product of powers with the same base:
![a^(m)a^(n)=a^(m+n)](https://img.qammunity.org/2020/formulas/mathematics/college/j2lu3raz6dlr4u4oomi4wrjp1mdivkos33.png)
Power of a power:
![(a^(m))^(n)=a^(m*n)](https://img.qammunity.org/2020/formulas/mathematics/college/mpwmk5nsrrvbc5wl4kfo6d51ewht9zfvwg.png)
Also, we must remember that if we want to introduce a number into a root, in order to not change the expression, we need to introduce it with the same exponent:
![a*√(b)=\sqrt{a^(2)*b }](https://img.qammunity.org/2020/formulas/mathematics/college/c3z5pr4k0501e4qskvj5i7ubix0sj4w9fc.png)
So, solving the problem, we have:
![\sqrt{3^(15) }=3^(7)*√(3)\\\\3^(7)*√(3)=\sqrt{(3^(7))^(2) *3}\\\\\sqrt{(3^(7))^(2) *3}=\sqrt{(3^(14) *3}\\\\\sqrt{3^(14) *3}=\sqrt{3^(14+1)](https://img.qammunity.org/2020/formulas/mathematics/college/51p9tepmpmxsch52qv7x9bwhs6i2ks65y4.png)
![\sqrt{3^(14+1) } =\sqrt{3^(15)}](https://img.qammunity.org/2020/formulas/mathematics/college/pf0l51b4f5gurezwqb3hyymukqddcmj4gp.png)
Hence,
![\sqrt{3^(15) }=3^(7)* √(3)](https://img.qammunity.org/2020/formulas/mathematics/college/ul2vvbmos2dqbhued956ia6uzjvc8q5ne4.png)
So, the correct option is D.
![\sqrt{3^(15) }=3^(7)* √(3)](https://img.qammunity.org/2020/formulas/mathematics/college/ul2vvbmos2dqbhued956ia6uzjvc8q5ne4.png)
Have a nice day!